Prompt-Based Automation of Agile Requirements Documentation: Design for Limited-Infrastructure Environment - Kruk, Roman; Zhukovska, Nataliia (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This study presents a proof-of-concept design and evaluation of a prompt-based automation approach for Agile requirements documentation in a limited-infrastructure environment. Building upon a previously proposed five-step LLM-based analytical framework, the research explores how structured prompt engineering can replicate the behavior of a full middleware system for transforming Jira exports into publishable Feature Specification Documents. The experiment involved 12 iterative prompt-refinement cycles applied to real project data. The final Gem’s configuration achieved 79% successful cases (improved by 27% when project knowledge artifacts were included). The results confirm that prompt-driven automation can effectively bridge unstructured Agile artifacts and formal specification, offering a lightweight and auditable alternative to traditional requirements documentation workflows.